Device engineering for high-performance, low-voltage operating organic field effect transistor on plastic substrate. (26th October 2017) - Houin, Geoffroy; Duez, Frédéric; Garcia, Luc; Cantatore, Eugenio; Hirsch, Lionel; Belot, Didier; Pellet, Claude; Abbas, Mamatimin
Abstract: Various aspects in device engineering were tackled to realize a high-performance, low-voltage operating organic field effect transistor on plastic substrate. Contact resistance between the active layer and metal electrodes was decreased by employing oxide interfacial layers. The anodization of the Al gate served as a high capacitance dielectric layer enabling low-voltage operation of the devices. Several polymers were investigated in passivating the surface of the oxide dielectric to decrease the interfacial trap densities and to enhance surface smoothness. Finally, using these optimum conditions, devices on plastic substrate were fabricated which yielded mobility higher than 2 cm 2 V −1 s −1 without hysteresis, operating below 5 V, with the current on/off ratio higher than 10 6 and the prospect of various applications in organic electronics.